Pectinolytic and Cellulolytic Enzymes Enhance Fusarium compactum Virulence on Tubercles Infection of Egyptian Broomrape - Olubukola O. Babalola (International Journal of Microbiology)
The use of enzyme could facilitate pathogen penetration into plant host. Here the combination of cellulase and pectinase was ascertained on the pathogenicity of F. compactum (1.4×106  propagules ml−1) on broomrape tubercles. F. compactum alone infected all the inoculated tubercles but did not kill any significant number. Infested tomato roots that were inoculated with mycelia plus pectinase (20 U ml−1) had over 50% tubercles dead one week after treatment. Those inoculated with mycelia plus cellulase (20 U ml−1) had above 60% mortality. Mixtures of mycelial plus the two enzymes (10 U ml−1 of each enzyme) showed synergy. The activity catalyzed by an enzyme is a measure of the amount of enzyme present. It was shown that, in a 1 mg (10 U mg−1) cellulase used, 0.055 mg pectinase (1.1 U mg−1) is present. This explains why mycelial plus cellulase mix contends with mycelial plus the two enzymes.